Some Implications of the Te Kotahitanga Model of Teacher Positioning - Anita Gutschlag (New Zealand Journal of Teachers' Work)
The Ministry of Education funded Te Kotahitanga project aims to improve the educational achievement of Māori students in mainstream secondary schools. However, it is contended that certain contradictions inherent in the original research project will limit its overall success. In particular, the implications of Te Kotahitanga’s ‘teacher positioning model’ are discussed. Such a model offers and allocates teachers only a prescribed set of discourse positions. This provides a false choice for teachers between ‘agency’ and ‘deficit theorising’. It is argued that alternative positions must be opened up for debate before Te Kotahitanga’s critical potential can be realised.